Prototyping einer Fahrzeug-steuerung in einer virtuellen 3D-Umgebung - Braatz, A.; Flake, Stephan; Müller, Wolfgang; Westkämper, E.
Prototyping mit 3D-Modellen in virtueller Umgebung ist eine kostengünstige Alternative zur Entwicklung von physikalischen Modellen und Mock-ups. Für einige Anwendungen ergeben sich erhebliche Vorteile durch die Validierung in einer virtuellen Umgebung. In diesem Artikel stellen wir den Einsatz einer 3D-Animation zur Entwicklung und zum Test einer Fahrzeugsteuerung vor. Basierend auf dem Prinzip der schrittweisen Verfeinerung kann die Steuerung zunächst nur unter Berücksichtigung der Kommunikation zwischen den Basiskomponenten entworfen werden. Im zweiten Schritt wird die Ansteuerung der Aktoren unter Auswertung der Sensoren berücksichtigt. Letztendlich ist das System unter Einflussnahme der physikalischen Größen zu validieren. Wir stellen die Schnittstelle exemplarisch anhand einer Steuerung für fahrerlose Transportfahrzeuge im Szenario eines holonischen Transportsystems vor.

Prevalence of chronic complications, metabolic control and nutritional intake in type 1 diabetes: comparison between different European regions. EURODIAB Complications Study group. - Toeller, M; Buyken, Anette; Heitkamp, G; Berg, G; Scherbaum, WA (Horm Metab Res)

Fiber intake, serum cholesterol levels, and cardiovascular disease in European individuals with type 1 diabetes. EURODIAB IDDM Complications Study Group. - Toeller, M; Buyken, Anette; Heitkamp, G; de Pergola, G; Giorgino, F; Fuller, JH (Diabetes Care)

Interkulturelle Bildung als Aufgabe haushaltsbezogenen Unterrichts - Schlegel-Matthies, Kirsten (Internationale Perspektiven in Hauswirtschaft und Haushaltswissenschaft. 20 Jahre Beirat. Dokumentations- und Diskussionsbeiträge)

Virtuelles Prototyping einer Robotersteuerung durch interaktive 3D-Simulation - Geiger, Christian; Lehrenfeld, G.; Müller, Wolfgang

Visual Specification, Modeling, and Illustrations of Complex Systems - Geiger, Christian; Lehrenfeld, G.; Müller, Wolfgang (Proceedings of HICSS-32)
This article introduces and discusses different innovative means for visual specification and animation of complex concurrent systems. It introduces the completely visual programming language Pictorial Janus (PJ) and its application in the customer-oriented design process. PJ implements a completely visual programming language with inherent animation facilities. The article outlines the transformation of purely visual PJ programs into textual imperative programming languages. The second part of the article investigates animated 3D-presentations and introduces a novel approach to an animated 3D programming language for interactive customer-oriented illustrations.
Keywords: Animation; Computer languages; Object oriented modeling; Collaboration; Process design; Graphical user interfaces; Jacobian matrices; Standardization; Feedback; Software prototyping

Scalable System for 3D Audio Raytracing - Müller, Wolfgang; Ullmann, F. (Proceedings IEEE International Conference on Multimedia Computing and Systems)
Though several approaches in sound processing are denoted as 3D audio very few of them generate high quality 3D audio information which allows listeners to exactly locate sound sources in three dimensional space. We present an approach to enhance sound by high quality 3D audio information through acoustic ray tracing where 3D audio is offline processed with digital filters of a head-related transfer function. The basic approach computes a fixed sound source for fixed listener. This approach is extended to generate 3D audio for moving listeners in interactive environments.
Keywords: Ray tracing; Loudspeakers; Motion pictures; Acoustic reflection; Ear; Digital filters; Parallel processing; Humans; Physics; Crosstalk

Relation of fibre intake to HbA1c and the prevalence of severe ketoacidosis and severe hypoglycaemia. EURODIAB IDDM Complications Study Group. - Buyken, Anette; Toeller, M; Heitkamp, G; Vitelli, F; Stehle, P; Scherbaum, WA; Fuller, JH (Diabetologia)

An Example of Task Oriented Empirical Evaluations of 3D-Display Modes - Volbracht, Sabine; Domik, Gitta; Shahrbabaki, Khatoun; Fels, Gregor (Journal of Universal Computer Science)

Beller, Walter, “Logic in Mexico”, In: Santiago Ramirez (ed.), Mexican Studies in the History and Philosophy of Science, Kluwer: Dordrecht 1995 (= Boston Stud. Philos. Sci.; 172), 1–22 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Berufsorientierung in Zeiten der Krise: Thematisierung - Dethematisierung. - Bigga, Regine (Schule und Arbeitswelt. Zwischen Thematisierung und De-Thematisierung von Geschlecht.)

Anregungen für die Lehrplanarbeit hinsichtlich der Gleichstellung der Geschlechter. Lehrpläne für Mädchen und Jungen. - Bigga, Regine (Lisa-Jahrbuch)

Authoring Communicating Agents in Virtual Environments - Geiger, Christian; Lehrenfeld, Georg; Müller, Wolfgang (Proceedings of the Annual Conference for the Computer Human Interaction)
3D-graphics popularity has steadily increased in a number of areas such as entertainment, scienti c vi- sualization, simulation, and virtual reality. Despite this rapid growth the authoring of animated 3D objects in virtual environments is stil l by no means trivial. This article presents new concepts of the animated 3D programming language SAM (Solid Agents in Motion) and its programming environment. In SAM, the main syntactic objects like agents, rules, and messages are represented as 3D objects. The design of a SAM pro- gram is supported by a dedicated 3D structure editor. The editor al lows the de nition and spatial arrange- ment of SAM agents in a 3D scene by direct manipu- lation. The paper gives a number of SAM examples, demonstrating the authoring of simple animated vir- tual 3D scenarios.

SAM - An Animated 3D Programming Language - Geiger, Christian; Müller, Wolfgang; Rosenbach, W. (Proceedings of the IEEE Symposium on Visual Languages)
This article presents the animated visual 3D programming language SAM (Solid Agents in Motion) for parallel systems specification and animation. A SAM program is a set of interacting agents synchronously exchanging messages. The agent's behaviour is specified by means of production rules with a condition and a sequence of actions each. Actions are linearly ordered and execute when matching a rule. In SAM, main syntactic objects like agents, rules, and messages are 3D. These objects can have an abstract and a concrete, solid 3D presentation. While the abstract representation is for programming and debugging, the concrete representation is for animated 3D end-user presentations. After outlining the concepts of SAM this article gives two programming examples of 3D micro worlds and an overview of the programming environment.
Keywords: Animation; Computer languages; Solids; Concrete; Application software; Virtual reality; Programming profession; Switches; Visualization; Debugging

Repeatability of three-day dietary records in the EURODIAB IDDM Complications Study. - Toeller, M; Buyken, Anette; Heitkamp, G; Milne, R; Klischan, A; Gries, FA (Eur J Clin Nutr)

Logik, Mathesis universalis und allgemeine Wissenschaft. Leibniz und die Wiederentdeckung der formalen Logik im 19. Jahrhundert - Peckhaus, Volker
Rezensionen: J. Legris, “Mathesis Universalis”, Mathesis 13 (1997), 167– 175; Zbl. Math. 884.01021 (R. Murawski); Philosophischer Literaturanzeiger 51 (1998), 114–117 (G. Schenk); MR 98h:01013 (H. Sinaceur); Peirce Project Newsletter 3 No. 1, 7; Philosophiegeschichte und logische Analyse. Logical Analysis and History of Philosophy, Bd. 2, Mentis: Paderborn 1999, 259–264 (W. Malzkorn); History and Philosophy of Logic 20 (1999), 67–69 (H. Linneweber-Lammerskitten); Erkenntnis 50 (1999), 133–136 (P. Mancosu); Berichte zur Wissenschaftsgeschichte 22 (1999), 207–208 (P. Mancosu); NTM. Schriftenreihe für Geschichte der Naturwissenschaften, Technik und Medizin N.S. 8 (2000), H. 1, 290 (K.-H. Schlote), 49–50; Anuario Filosofico 32 (1999), 853–854; M.F., “La logica di Leibniz nel XIX secolo”, Giornale critico della filosofia Italiana 6 ser. 20 (2000), 161–164; Archiv für Geschichte der Philosophie 82 (2000), 349–352 (R. Vilkko); Epistemologia 24 (2001), 152–155 (M. Ferriani); The Review of Modern Logic 9, nos. 3 & 4 (2003–2004), 119–122 (H. Frank).

Rademacher, Ulf: Der Europäische Betriebsrat. Die Richtlinie 94 / 45 / EG des Rates vom 22. 4. 1994 und ihre Umsetzung in nationales Recht; Nomos: Universitätsschriften Recht 1997 - Krimphove, Dieter (Recht der Arbeit (RdA))

How effective are 3D display modes? - Volbracht, Sabine; Domik, Gitta; Shahrbabaki, Khatoun; Fels, Gregor (Proceedings of the ACM SIGCHI Conference on Human factors in computing systems)

Blinde Flecken in der Berufsorientierung im Rahmen der Arbeitslehre. Zusammenhang von Erwerbsarbeit und Hausarbeit fehlt nach wie vor. - Bigga, Regine (Hauswirtschaftliche Bildung)

Visual-Textual Prototyping of 4D Scenes - Dücker, M.; Geiger, Christian; Hunstock, R.; Lehrenfeld, Georg; Müller, Wolfgang (Proceedings of the 1997 IEEE Symposium on Visual Languages)
3D-graphics are becoming popular in a steadily increasing number of areas such as entertainment, scientific visualization, simulation, and virtual reality. Despite this rapid growth the generation of animated 3D scenes is by no means trivial. Since animated 3D objects evolve over time the authors denote these objects as 4D. The article presents a novel approach to the rapid prototyping of 4D models. They introduce the AAL (Animated Agent Layer) system. AAL is an interpreter-based approach covering a textual (AAL-PR) as well as a visual command language (AAL-VL) for the specification of the dynamics in 4D scenes. AAL provides support for different levels of abstraction: primitives, structured objects, animated objects, and animated (autonomous) agents.
Keywords: Prototypes; Layout; Animation; Command languages; Application software; Libraries; Virtual reality; Computer graphics; Hardware; Context modeling

Nutritional intake of 2868 IDDM patients from 30 centres in Europe. EURODIAB IDDM Complications Study Group. - Toeller, M; Klischan, A; Heitkamp, G; Schumacher, W; Milne, R; Buyken, Anette; Karamanos, B; Gries, FA (Diabetologia)

An Experimental Comparison of 3D Display Modes - Volbracht, S.; Domik, Gitta; Shahrbabaki, K.; Fels, G. (Proceedings of IEEE Visualization)

3d core-level shifts at - Schmidt, Wolf Gero; Käckell, P.; Bechstedt, F. (Surface Science)

Se-induced 3d core-level shifts of GaAs(110) - Käckell, Peter; Schmidt, Wolf Gero; Bechstedt, Friedhelm (Applied Surface Science)

De Caro, Mario, “Galileo’s Mathematical Platonism”, in: Czermak (Hg.) 1993 [Zbl 0836.00022], 13–22 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Franchella, Miriam, “L.E.J. Brouwer: Toward Intuitionistic Logic”, Historia Mathematica 22 (1995), 304–322 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Casati, Roberto/Smith, Barry/White, Graham (Hgg.), Philosophy of the Cognitive Sciences. Proceedings of the 16th International Wittgenstein-Symposium, 15–22 August 1993, Kirchberg am Wechsel, Austria, Hölder-Pichler-Tempsky: Wien 1994 (= Schriftenreihe der Wittgenstein-Gesellschaft; 21) - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Sicherheitserziehung - ein Thema für den Arbeitslehreunterricht. - Bigga, Regine (ARBEIT UND TECHNIK in der Schule)

Visual Modeling and 3D-Representation with a Complete Visual Programming Language --- A Case Study in Manufacturing - Geiger, Christian; Hunstock, R.; Lehrenfeld, Georg; Müller, Wolfgang; Quintanilla, J.; Tahedl, C.; Weber, A. (Proceedings of the 1996 IEEE Symposium on Visual Languages)
The main goal of the article is to evaluate the suitability of visual programming languages, i.e., Pictorial Janus (K. Kahn and V. Saraswat, 1990), for the modeling of complex systems and their control strategies. These systems can be seen as networks of communicating objects. Objects select strategies for suitable actions based on incoming messages. Our field of investigation is in computer integrated manufacturing considering the example of a car manufacturing cell. This color sorting assembly buffer (CSAB) schedules jobs in queues. The jobs represent car bodies scheduled in feeder lines for the enameling. Feeder lines collect raw bodies to blocks. Blocks are bodies which are to be enameled by the same color. This organization decreases the cost of expensive change-over-times when changing colors at the enamelling. Blocks of bodies are dislocated from the queue and enameled successively. Contradictory system goals, such as minimizing color changes and preserving the sequence of incoming jobs, have to be regarded by appropriate control strategies. Due to the complexity of this (NP complete) problem and to real time requirements for online control there are no optimal strategies on hand. Consequently, suitable heuristics have to be developed. Often they are designed applying a trial-and-error method. A modeling framework has to support the rapid prototyping of these systems as well as an expressive end user oriented representation. Both are essential requirements since end users need other visualization techniques than experienced designers due to their different knowledge and interests.
Keywords: Computer integrated manufacturing; Job shop scheduling; Processor scheduling; Computer languages; Control system synthesis; Computer aided manufacturing; Sorting; Assembly; Costs; Control systems

Computergestützte Intervention bei Rechtschreibschwäche: Effekte eines kognitions- und lernpsychologisch orientierten Trainingsprogramms auf Morphembasis bei sehr schwachen Sonderschülern. - Walther, J.; Bigga, Regine; Bischof, H. (Sonderpädagogik)

Weak Sequential Composition in Process Algebras - Rensink, Arend; Wehrheim, Heike (CONCUR '94, Concurrency Theory, 5th International Conference, Uppsala, Sweden, August 22-25, 1994, Proceedings)

Wozu Algebra der Logik? Ernst Schröders Suche nach einer universalen Theorie der Verknüpfungen - Peckhaus, Volker (Modern Logic)
Abstract: Historia Mathematica 22 (1995), #22.2.62 (I. Anellis). Rezensionen: Zbl. Math. 812.01012 (I. Grattan-Guinness); MR 95m:03002 (M. Guillaume).

Die Gleichstellung der Geschlechter im Lehrplan. Anregungen für Schule und Unterricht. - Bigga, Regine; Braun, F.; Hoffmann, L.

Erwerbsarbeit - Hausarbeit. Strukturwandel der Arbeit als Herausforderung an das Lernfeld Arbeitslehre - Tornieporth, G.; Bigga, Regine

Ergebnisse aus dem Projekt Mädchen & junge Frauen in der Arbeitswelt - Bigga, Regine (Erwerbsarbeit - Hausarbeit. Strukturwandel der Arbeit als Herausforderung an das Lernfeld der Arbeitslehre)

The Development of Ernst Schröder’s Attitude towards Logic [Abstract] - Peckhaus, Volker (XIXth International Congress of History of Science. 22–29 August 1993 Zaragoza (Spain). Book of Abstracts Symposia)

Leibniz’ ,Mathesis universalis‘ und die Mathematiker des 19. Jahrhunderts [Abstract] - Peckhaus, Volker (Fachsektion Geschichte der Mathematik der Deutschen Mathematiker-Vereinigung. Sektionstagung vom 22. bis 26. März 1993 in Wuppertal)

Forschungsergebnisse zur Geschlechterfrage - Konsequenzen für die Gestaltung von Unterricht sowie für die Aus- und Weiterbildung von Lehrkräften - Bigga, Regine (Lehrplanrevision in Schleswig-Holstein)

Die deutschsprachige Literatur Osteuropas und ihre Rezeption in der Bundesrepublik. Probleme und Chancen einer 'kleinen Literatur' - Eke, Norbert Otto (Deutsche Studien 29)
Auch erschienen in: Neue Zeitung [Budapest], Nr 28 vom 14.7.1990, S. 6-7, und Nr 29 vom 21.7.1990, S. 8-9, sowie Neue Literatur [Bukarest], H. 5-6/1990/91, S. 22-42

Berufsorientierung für Mädchen zwischen ,,typisch weiblichen" und ,,typisch männlichen" Berufen. - Bigga, Regine (Arbeitslehre und Polytechnik: Annäherung und Wandel. Beiträge zur technisch-ökonomischen Allgemeinbildung im vereinten Deutschland.)

Berufswahlverhalten und Lebensplanung von Mädchen. Ein Thema für die Schule und eine Aufgabe für die Gewerkschaften. - Bigga, Regine (Gewerkschaftliche Bildungspolitik)

Sexismus am Arbeitsplatz - Ein Tabuthema der Arbeitslehre. - Bigga, Regine (awt-info)

Friedhof als Quelle historischen Arbeitens. Der Eichhof Friedhof in Kiel/Kronshagen - Bigga, Regine; Colmorgen, Eckhard; Danker, Uwe; Dittrich, Irene (Beirat für Geschichte der Arbeiterbewegung und Demokratie in Schleswig-Holstein)

Erstellung einer Ton-Dia-Schau zum Einsatz im schulischen Unterricht für den Kreis Lippe zum 40. Jubiläum des Art. 3 Abs. 2 Grundgesetz “Männer und Frauen sind gleichberechtigt” - Schlegel-Matthies, Kirsten

Karl Eugen Müller (1865–1932) und seine Rolle in der Entwicklung der Algebra der Logik - Peckhaus, Volker (History and Philosophy of Logic)
Abstracts: The Philosopher's Index. Cumulative Edition 22 (1988), 509–510; Historical Abstracts 40A:4245. Rezensionen: Zbl. Math. 645.01019 (R. Murawski); MR 89e:01038 (Chris Brink).

Studium Arbeitslehre - Rückblick mit Ausblick - Bigga, Regine (Arbeitslehre / Polytechnik: Ein Beitrag zur Neuen Allgemeinbildung. Die Geschichte von Arbeit, Technik und Produktion im Unterricht)

Die Schleswig-Holsteinische Volkszeitung 1892 bis 1968 - Facetten aus ihrer Geschichte - Bigga, Regine; Danker, Uwe (Beirat für Geschichte der Arbeiterbewegung und Demokratie in Schleswig-Holstein)

Der VZ - Verlag in Photographien - Bigga, Regine; Danker, Uwe; Bruhn, Paul (Beirat für Geschichte der Arbeiterbewegung und Demokratie in Schleswig-Holstein)

Anschauliches Lernen im Museum. - Bigga, Regine (Allgemeinbildung und Arbeit, Technik, Wirtschaft - Innovationen in Curriculum und Schul-Praxis.)

Geschlechtsspezifische Arbeitsteilung und technische Innovation - Neue Technologien, Frauenerwerbsarbeit und historisch-genetisches Lernen über Arbeit und Technik. - Bigga, Regine; Oberliesen, R. (Neue Technologien und technisch-ökonomische Bildung.)